ANALISIS PENGARUH KUALITAS PELAYANAN, KUALITAS WEBSITE TERHADAP KEPUASAN, KEPERCAYAAN, DAN NIAT PEMBELIAN KEMBALI (Studi pada toko online Blibli.com) - Novinoa, Galuh; Sutopo, Sutopo (Faculty of Economics and Business Diponegoro University, 2017)
This study aimed to analyze the effects that arise from the service quality and website quality on customer satisfaction, and trust, its influence on repurchase intention from Blibli.com. Variables used in this study is service quality and website qualityÂ as an independent variable, and customer satisfaction and trust as an intervening variable lastly, the repurchase intention as the dependent variable. The sample in this study were 171 respondents from the consumer of Blibli.com.The method used is non- probability purposive sampling by distributing e-questionnaires to the respondents (customer). In this study developed a theoretical model to propose six hypotheses to be tested using analysis tools Structural Equation Modeling (SEM) which is operated through a program AMOS 24.0. Based on the research of data processing SEM for full model has met the criteria of goodness of fit as follows, the value of chi-square = 134,089; probability = 0,076; RMSEA = 0,034; CMIN/DF = 1,197; GFI = 0,915; TLI = 0,983; CFI = 0,986; and a marginal criteria which is AGFI = 0,883. With the result, it can be said that this model is feasible to be used. The results showed that the repurchasse intention can be improved by increasing website quality that affect the trustÂ as a determinant of success to increase repurchase intention.